LEGAL PLURALISM AND TEXTUALISM: CONTRASTING APPROACHES TO ISLAMIC INHERITANCE LAW IN INDONESIA AND OMAN - Taufiq, Taufiq; Kunantiyorini, Anik; Soeharto, Achmad; Wibowo, Dwi Edi; Ezzerouali, Souad Ahmed (Universitas Syiah Kuala, 2025)
Islamic inheritance law highlights diverse approaches to its interpretation and implementation in Muslim-majority countries such as Indonesia and Oman. These differences arise from a legal gap between the universal principles outlined in the Qur'an and their application within national legal frameworks. In Indonesia, Islamic inheritance law functions within a pluralistic legal system, whereas in Oman, Sharia principles serve as the primary and integral foundation of the judiciary. This article examines how the foundational philosophy of Islamic inheritance law is understood and applied in Indonesia and Oman, two countries with contrasting legal systems, to identify both normative and practical challenges, as well as the implications of these differences for future legal development. Employing a normative and comparative legal approach, the study reviews relevant legislation, fatwas, and court decisions in both countries, alongside an analysis of classical and contemporary Islamic jurisprudence. The findings indicate that Indonesia adopts a conciliatory approach, balancing religious norms with modern social needs, while Oman tends to adhere to a more literal and textual interpretation of inheritance law. These differences reflect the dynamic nature of Islamic inheritance law philosophy in responding to each country's unique social, cultural, and political contexts. This contributes to the ongoing discourse on developing an adaptive and context-sensitive understanding of Islamic inheritance law within various national legal systems.